Flexible Diazide Based Sulfonated Polytriazoles and Their Proton Exchange Membrane Properties. Issue 14 (8th May 2017) - Saha, Sayantani; Banerjee, Susanta; Komber, Hartmut; Voit, Brigitte
Abstract : A series of sulfonated polytriazoles with high ion exchange capacity are successfully synthesized by the click polymerization. The films of these polymers exhibit high thermal, chemical, and mechanical stability and very high proton conductivity up to 225 mS cm −1 at 80 °C in hydrated condition. Abstract : The preparation, characterization, and property evaluation of a series of new semifluorinated polytriazoles (PTEHSH‐XX) with various degrees of sulfonation is described. The polymers are synthesized by the click polymerization reaction of a mixture of a new diazide monomer, 1, 4‐bis‐[2′‐trifluromethyl 4′‐(4″‐azidophenyl)phenoxy]phenyl, and a sulfonated monomer, 4, 4′‐diazido‐2, 2′‐stilbenedisulfonic acid disodium salt, with an equimolar amount of a dialkyne monomer, 1, 3‐diethynylbenzene. The polytriazoles are characterized by Fourier transform infrared spectroscopy (FTIR) and NMR spectroscopic techniques. The polytriazoles show good solubility in selective organic solvents and film forming ability. The films prepared from these polymers show high thermal and chemical stability, low water uptake, high dimensional stability, and excellent mechanical properties. The transmission electron microscopy images of these polymers exhibit a uniformly phase separated morphology. The polymers show very high proton conductivity and the values are within the range of 27–118 mS cm −1 at 30 °C, 53–225 mS cm −1 at 80 °C, and 58–235 mS cm −1 at 90 °C in hydrated condition.